ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH STUDI PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ranti Fellia Anzani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine and analyze the comparison of the financial performance of BUMN Conventional Banks and BUMN Sharia Banks during the 2015-2019 period based on liquidity ratios, solvency ratios and profitability ratios. As well as to determine the fulfillment of financial performance standards for BUMN Conventional Banks and BUMN Sharia Banks based on liquidity ratios, solvency ratios and profitability ratios during the 2015-2019 period using financial ratios Loan to Deposit Ratio (LDR) and Finanicing Deposit Ratio (FDR), Capital Adequacy Ratio. (CAR), Return on Assets (ROA), Return on Equity (ROE) and Operating Expenses Operating Income (BOPO).This study uses secondary data in the form of data obtained by the author from the Financial Statements of Bank BRI, BNI and Mandiri as well as Bank BRI Syariah, BNI Syariah and Bank Syariah Mandiri which were obtained from the Riau Branch Indonesia Stock Exchange Office in the Sudirman Business Central Complex Blok B1.The results of the analysis show that the analysis of the financial performance of a state-owned conventional bank using bank financial ratios has the ability to "good" in fulfilling capital adequacy, generate profit and efficiency in operating costs, but "not good" in managing loans with funds received by the third party. BUMN Sharia Banks have "good" capabilities in managing financing and are provided with funds received by third parties, meeting capital adequacy and efficiency of operating costs, but are "not good" in obtaining the resulting profit.